(untitled) (Conferencea, 2022)
Innovations are one of the most important factors of modernizing and diversifying the economy, ensuring its rapid development and competitiveness, further increasing the country’s position and influence in the world community. For this reason, today every country is paying great attention to the wide use of innovation opportunities to ensure the stability of its economy and increase the well-being of the population. For this purpose, priority has been given to the implementation of targeted projects on the modernization and technical renewal of the main sectors of our economy in our republic, the introduction of modern innovation technologies that will provide a strong impetus for our country to achieve new goals and ensure its competitiveness in the world market. Implementation of innovation projects is directly related to investments.